Investigation on regulation of N-acetyltransferase 2 expression by nuclear receptors in human hepatocytes - Hong, Kyung U.; Aureliano, Anthony P.; Walls, Kennedy M.; Hein, David W. (Frontiers in Pharmacology, 2024)
Arylamine N-acetyltransferase 2 (NAT2) expresses a well-defined genetic polymorphism in humans that modifies drug and xenobiotic metabolism. Recent studies and genome wide association studies have reported that genetic variants of NAT2 are associated with differential risks of developing dyslipidemia and cardiometabolic disorders, suggesting a previously unrecognized role of NAT2 in pathophysiology of metabolic disorders. In support of this notion, we recently showed that human NAT2 expression is differentially regulated by glucose and insulin. Moreover, our in-silico analysis showed that NAT2 is co-expressed with nuclear receptors enriched in the liver, e.g., NR1H4 (FXR) and NR1I2 (PXR), that have been previously implicated in regulation of hepatic glucose and lipid homeostasis. Identification of transcriptional regulator(s) of human NAT2 would aid in understanding novel functions that it may play in the liver. Thus, the present study was designed to investigate if NAT2 is transcriptionally regulated by hepatic nuclear receptors. To test this, we treated cryopreserved human hepatocytes with agonists towards four different hepatic transcription factors/nuclear hormone receptors, namely FXR (NR1H4), PXR (NR1I2), LXR (NR1H3), and PPARα (PPARA), and measured their effects on the level of NAT2 mRNA. While the treatment with a FXR, PXR, or LXR agonist (i.e., GW-4064, SR-12813, or GW-3965) significantly induced their respective target genes, treatment with these agonists did not significantly alter the transcript level of NAT2 in human hepatocytes. PPARα agonist, GW-7647, treatment resulted in a statistically significant decrease in the NAT2 transcript level. However, its magnitude was marginal. In summary, hepatic nuclear receptors we examined in the present study (FXR, PXR, LXR, and PPARα) did not significantly alter NAT2 expression in cryopreserved human hepatocytes. Additional studies are needed to identify transcriptional regulators of hepatic NAT2 expression.